2004
DOI: 10.1051/agro:2003055
|View full text |Cite
|
Sign up to set email alerts
|

Root-reducing capacity, rhizosphere acidification, peroxidase and catalase activities and nutrient levels of Citrus taiwanica and C. volkameriana seedlings, under Fe deprivation conditions

Abstract: -The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
6
13
0
5
Order By: Relevance
“…Leaf CAT activity has been also referred to be significantly higher than the root one in maize (Redinbaugh et al, 1990) and barley (Azevedo et al, 1998). On the other hand, the enzyme activity of Citrus young roots has been reported to be higher than the leaves' one (Chouliaras et al, 2004). We also found that in younger plants leaf CAT activity is equal or higher (at high N nutrition) than in older ones (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Leaf CAT activity has been also referred to be significantly higher than the root one in maize (Redinbaugh et al, 1990) and barley (Azevedo et al, 1998). On the other hand, the enzyme activity of Citrus young roots has been reported to be higher than the leaves' one (Chouliaras et al, 2004). We also found that in younger plants leaf CAT activity is equal or higher (at high N nutrition) than in older ones (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The bicarbonate ion can influence Fe reduction in the roots during Fe uptake and Fe transport or metabolism within the plant (Zuo et al 2000). Decrease in FCR activity in response to bicarbonate has been reported previously for conventional growth citrus (Chouliaras et al 2004). It is well known that H + -ATPase in plasma membrane plays an important role in the transport of multiple ions (Palmgren & Harper 1999), and there are investigations indicating that NO could induce H + -ATPase activity (Cui et al 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Sin embargo, otros estudios en peral ), vid (Ksouri et al, 2007, cacahuete (Zuo et al, 2007), Arabidopsis (Msilini et al, 2009) y guisante (Jelali et al, 2010b) muestran resultados concordantes con los nuestros; de manera que, las plantas +FeBic aumentan la actividad FC-R de sus raíces, pero sin alcanzar los niveles detectados en las plantas cultivadas sin Fe. Finalmente, otros informes en plantas de cítricos y melocotonero a los que se suministró HCO 3 -en concentración elevada recogen una reducción de dicha actividad FC-R (Chouliaras et al, 2004a;Molassiotis et al, 2006). No obstante, estos mismos autores, trabajando con portainjertos de cítricos, observaron que tanto las raíces de las plantas cultivadas con una solución nutritiva sin Fe, con un bajo suministro de Fe o con adición de HCO 3 -manifestaron un aumento de la capacidad de reducción, en comparación con la actividad encontrada en las raíces de las plantas con un suministro adecuado de Fe (Chouliaras et al, 2004b).…”
Section: Discussionunclassified
“…Finalmente, otros estudios indicaron que una elevada concentración de HCO 3 -en la solución nutritiva puede reducir la actividad FC-R en árboles +FeBic de cítricos y melocotonero (Chouliaras et al, 2004a;Molassiotis et al, 2006). Así mismo, el tratamiento con HCO 3 -provocó una mayor actividad de la enzima H + -ATPasa en raíces de plantas +FeBic de guisante (Jelali et al, 2010b) y de peral, pero no en varios genotipos de membrillero .…”
Section: Discussionunclassified
See 1 more Smart Citation